Desain Pembelajaran Campuran (Blended Learning) pada Materi Determinan dan Invers Matriks - Novita Albab; Hakim Lukman El (Griya Journal of Mathematics Education and Application, 2022)
This article presents the development of blended learning designs for the subject of determinant and inverse of a matrix for class X. Learning development is carried out using needs analysis, student analysis, and task analysis. Performance objectives and learning outcomes are discussed in detail and adjusted to the learning objectives. The conclusion of this article is that blended learning design is recommended for the subject of determinant and inverse of a matrix. This is because this design can increase the motivation and activity of students and the interaction between teachers and students as well as interactions between students, so that mathematical understanding and problem-solving abilities are also increased.